Indoor radon measurements in six Latin American countries - Canoba, A.; López, F. O.; Arnaud, M. I.; Oliveira, A. A.; Neman, R. S.; Hadler, J. C.; Iunes, P. J.; Paulo, S. R.; Osorio, A. M. [UNESP]; Aparecido, R. [UNESP]; Rodríguez, C. [UNESP]; Moreno, V.; et al. (My University, 2002)
Most of the natural radiation dose to man comes from radon gas and its progeny. Several countries have established national institutions and national programs in charge of the study of radon and its connection with lung cancer risk and public health. In this paper an indoor radon measurements in Latin American countries is presented. The participants in this work were from Argentina, Brazil, Ecuador, Mexico, Peru and Venezuela. Many different techniques are used in this common effort, and the indoor radon levels in specific locations in each of the participant countries are presented.
Keywords: Indoor radon; Latin American countries; Radon detection; indoor air; radon